Penerapan Model Pembelajaran Berbasis Proyek (PjBL) untuk Meningkatkan Keterampilan Proses Sains. - M. Syahrul Romadhoni (Universitas Muhammadiyah Makassar, 2026)
Abstract Science Process Skills (SPS) are important competencies in science learning because they serve as the basis for developing students' scientific thinking abilities. However, in many schools, science learning is still theoretical and does not provide enough space for students to conduct scientific exploration. This study aims to determine the effectiveness of the Project Based Learning (PjBL) model in improving students' science process skills. The study used a library research method by analyzing accredited national journals and Indonesian science education books. The results of the study show that PjBL consistently improves SPS, such as the ability to observe, formulate problems, design experiments, interpret data, and communicate research results. PjBL also motivates students to be more active, creative, and able to solve real-world problems. Thus, PjBL is recommended as an alternative learning model to improve the quality of science learning in schools. Keywords: Project Based Learning, science process skills, science learning. Abstrak Keterampilan Proses Sains (KPS) merupakan kompetensi yang sangat diperlukan dalam pembelajaran IPA untuk membentuk kemampuan berpikir ilmiah siswa melalui kegiatan observasi, eksperimen, analisis, dan komunikasi. Namun, pembelajaran IPA di sekolah dasar masih cenderung berpusat pada guru dan minim kegiatan penyelidikan, sehingga perkembangan KPS belum optimal. Penelitian ini bertujuan menganalisis efektivitas model Project Based Learning (PjBL) dalam meningkatkan KPS siswa berdasarkan hasil studi kepustakaan terhadap jurnal nasional terakreditasi dan buku-buku pendidikan Indonesia. Hasil kajian menunjukkan bahwa PjBL mampu meningkatkan seluruh aspek KPS, termasuk keterampilan mengobservasi, merumuskan hipotesis, merancang eksperimen, menginterpretasi data, serta mengkomunikasikan hasil. PjBL juga dapat meningkatkan motivasi belajar, kolaborasi, dan kreativitas siswa. Dengan, PjBL layak diterapkan sebagai model pembelajaran alternatif dalam meningkatkan kualitas pembelajaran IPA di sekolah dasar. Kata Kunci : Project Based Learning, Keterampilan Proses Sains, Pembelajaran IPA